2009
DOI: 10.1002/pssc.200881234
|View full text |Cite
|
Sign up to set email alerts
|

Characteristics of chemical bond and vacancy formation in chalcopyrite‐type CuInSe2 and related compounds

Abstract: We studied characteristics of chemical bond and vacancy formation in chalcopyrite‐type CuInSe2 (CIS) by first principles calculations. The chalcopyrite‐type CIS has two kinds of chemical bonds, Cu‐Se and In‐Se. The Cu‐Se bond is a weak covalent bonding because electrons occupy both bonding and antibonding orbitals of Cu 3d and Se 4p and occupy only the bonding orbital (a1) of Cu 4s and Se 4p and do not occupy the antibonding orbital (a1*) of Cu 4s and Se 4p. On the other hand, the In‐Se bond has a partially co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
43
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 28 publications
(43 citation statements)
references
References 10 publications
0
43
0
Order By: Relevance
“…In CIGS and CZTS, the non-Cu-cation-s/anion-p hybridized bonding states occur a lot deeper in the VB and have no overlap with the Cu d states and no contribution to the VBM; this increases the IP. 133,146 As a result of the similarities with CAS, 36 it is clear that this bonding regime is an inherent characteristic of this materials family.…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…In CIGS and CZTS, the non-Cu-cation-s/anion-p hybridized bonding states occur a lot deeper in the VB and have no overlap with the Cu d states and no contribution to the VBM; this increases the IP. 133,146 As a result of the similarities with CAS, 36 it is clear that this bonding regime is an inherent characteristic of this materials family.…”
Section: Resultsmentioning
confidence: 97%
“…These additional states alter the band alignments, raising the VBM somewhat, marginally lowering the IP, and generating band misalignment with other absorbers, seen in Figure , which is thought to be substantial in its effects in PV devices. In CIGS and CZTS, the non-Cu-cation-s/anion-p hybridized bonding states occur a lot deeper in the VB and have no overlap with the Cu d states and no contribution to the VBM; this increases the IP. , As a result of the similarities with CAS, it is clear that this bonding regime is an inherent characteristic of this materials family.…”
Section: Results and Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…However, the full merit of this practice is questioned when it is clear that the crystal structure of CAS is so different from CIGS, then so should be the DoS as the bonding is what leads to the adopted crystal structure. Clearly, from the CBDoS, Sb 5p states are the main cation contributor in CAS, whereas in CIGS, the bottom of the CB is mainly In/Ga s states [83][84][85] . Consequently, this has been recognised previously and found to be the reason why CAS shows superior absorption to CIGS 86 , but no further discussions have been made 33 .…”
Section: Density Of Statesmentioning
confidence: 99%
“…It was reported that the reductions in CGI and GGI are strongly related to the E A and I P . 61,62 The estimated CGI and GGI by XPS decreased from 0.39 to 0.18 and from 0.33 to 0.07 in XPS analysis, as shown in Figure 3, respectively. The changes in E A and I P for our epi-CIGSe by KF-PDT can be explained qualitatively by the reduction in CGI and GGI.…”
Section: ■ Theoretical Backgroundmentioning
confidence: 89%